Learning Affects Host Preference in Tsetse Flies - J. Bouyer; D. Cuisance; S. Messad; P. M. Guérin (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2005)
Tsetse flies are very efficient cyclic vectors of African trypanosomosis. Since tsetse are generally infected by the first blood meal, as in the case of sleeping sickness for example, any propensity to feed on the same host a second time will improve transmission within this host species, whereas transmission between host species will decrease. To test this hypothesis we presented a monitor lizard and a cow in a stable to marked tsetse flies that had first fed on one of these two hosts. 80% of the teneral flies that fed did so on the cow when provided the choice. Among the flies having feeding experience, a disproportionately high number of flies that had fed on one host returned to this host for the second meal. We discuss the energetic advantages of such a learning behavior and its importance in sleeping sickness epidemiology. The findings are of relevance to the role played by such learning behavior in disease transmission by other insect vectors of zoonoses.